Rule of law and judicial independence - Jo\~ao Carlos Trindade (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The rule of law and judicial independence are a project yet to be achieved in Mozambique. The different attempts made so far to reform the legal system, mainly after the change in political and strategic direction brought about by the Constitution of 1990, were always short-sighted and conjunctural in nature, under domestic and foreign pressure that was not always clear or well-intentioned. Real structural reforms need to be made for the judiciary to be able to affirm itself as a real power and, in this way, favour balanced growth of companies, increased productivity, investment and jobs and, at the same time, the defence of the rights and legitimate interests of individuals and groups with fewer economic resources.
Keywords: K40; 330; economic development; rule of law; judicial independence; Mozambique; judicialreform